Fuzzy Technique Application in Selecting Photovoltaic Energy and Solar Thermal Energy Production in Belt and Road Countries. (September 2021) - Qian, Xiaoyan; Bai, Yang; Huang, Weilun; Dai, Jie; Li, Xuan; Wang, Yuanzhu
Abstract: The fuzzy analytical hierarchy process and technique for order preference by similarity to an ideal solution are combined to select the best production location for photovoltaic energy and solar thermal energy in different regions. Case studies of countries with the Chinese Belt and Road Initiative are used to demonstrate this best production location selection process. The results show that the optimal production candidate for the production projects of photovoltaic energy and solar thermal energy should have satisfactory performance in the natural environment, energy demand gap, institutional stability, economic growth, social security, and public attitudes. However, this result should be different for different stakeholders; policymakers are advised to implement different selection strategies for solar thermal energy and photovoltaic energy projects.